Contributions of the Pedagogical Residency Program for the initial formation of Mathematics Graduates (Research, Society and Development, 2020)
The Pedagogical Residency Program is part of the National Teacher Formation Policy and aims at improving the quality of initial formation, as well as to enable students to have greater contact with schools, starting from the second half of the course. As such, the question which guided this research was: What are the contributions the Pedagogical Residency Program has been providing to Mathematics graduates in their initial formation? In order to answer it, the central objective was to analyze the contributions of this program to the formation of undergraduate students in Mathematics at a Federal Institution. Authors like Garcia (1999), Ponte (2002), Fiorentini & Castro (2003), among others, composed the theoretical framework. The qualitative research with case study traits was developed in 2019.1 with undergraduates who participated in the first program offer. For data collecting, a questionnaire with subjective questions was used and, for data analysis, Minayo's (2016) phases were used. The results point to the importance of collaborative work between the actors, the residents' awareness of aligning theory and practice and the concept of teaching as a continuum. Thus, the importance of developing actions, projects and other programs that enable greater experiences, reflections and (co)existence of the undergraduates with the school is supported.